Inteligencia emocional y su relación con el estilo de liderazgo de los directivos del Gobierno Autónomo Descentralizado Municipal del cantón Pujilí. - Cuyo Cayo, Darwin Estuardo (2020)
The purpose of this research is to analyze the relationship between emotional intelligence and leadership styles of the Directors of the Directorates of the Municipal Decentralized Autonomous Government of Canton Pujilí; focused on 31 heads and departmental managers. Through a qualitative-quantitative approach that seeks the documentary and field bibliographic modality, in order to collect the information according to the reagents, one of them is Trait Meta-Mood Scale (TMMS-24) that measures emotional intelligence whose results adduce have adequate emotional clarity this through the descriptive statistic of the means of the three dimensions studied such as emotional attention, emotional clarity and emotional repair, so also the leadership was worked with the reagent of the Leadership Styles of the Central American Institute of Administration of Companies (INCAE), whose result reflects a weak leadership in group and task activities, therefore there is a relationship between emotional intelligence and the leadership of public servants, therefore it is proposed to develop leadership workshops in the Directors of the Departments of the Municipal Decentralized Autonomous Government of Canton Pujilí, with the p The purpose of establishing techniques for strengthening leadership with the guidelines of leadership skills and decision making.